Content Analysis Untuk Menetapkan Konsep Penting Financial Technology (FINTECH) - Lukman Hakim Harsono (Faktor Exacta, 2019)
Abstract. This research discusses the development and fintech environment in this time. There are 505 data extracted from various online news websites which include detik.com, liputan6.com and cnnindonesia.com. All sources of news concerning fintech are collected with webharvy 5.2 which are then processed with atlas.ti 6.2 to count the number of words. The result of the calculation are turned into 10 concepts and will eventually figure out which concept is the most important. The concepts consists peraturan, indonesia, keuangan, perusahaan, teknologi, produk, fintech, layanan, masyarakat, and resiko. The research methods used for this research are both qualitative and quantitative research method. The quantitative research method is used when collecting data and the qualitative research method is used to process the data as well as the calculation of connection between each concept using SPSS22. The result of the connection test is virtually made with network connection. Based on the results, the concept peraturan is the most important concept of fintech. "Konsep peraturan" is related to 6 concepts which include fintech, product, risks, services, society and money.